2014
DOI: 10.1186/2251-6581-13-40
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal glycaemic and blood pressure control and screening for diabetic complications in adult ambulatory diabetic patients in Uganda: a retrospective study from a developing country

Abstract: BackgroundCurrently, Sub Saharan Africa is faced with a substantial burden from diabetes mellitus. In most of the African countries, screening for diabetes related complications and control of blood pressure and glycaemic levels is often suboptimal.The study aimed at assessing the extent of optimal glycaemic and blood pressure control and the frequency of screening for diabetic complications in adult ambulatory Ugandan diabetic patients.MethodsThis was a retrospective study of 250 medical records of adult diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
56
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 11 publications
(27 reference statements)
9
56
0
Order By: Relevance
“…Similar to other studies in SSA (Kibirige et al, 2014;Sobngwi et al, 2012), our current study found that glycemic control in our sample was suboptimal. Also in the current study, we found that women are more likely to have lower Hba1c on average; however, we are unable to make an inference about gender differences in actual glycemic control because only one man had achieved glycemic control.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to other studies in SSA (Kibirige et al, 2014;Sobngwi et al, 2012), our current study found that glycemic control in our sample was suboptimal. Also in the current study, we found that women are more likely to have lower Hba1c on average; however, we are unable to make an inference about gender differences in actual glycemic control because only one man had achieved glycemic control.…”
Section: Discussionsupporting
confidence: 89%
“…This can be explained by the varied study diagnostic approaches of PAD with higher prevalence noted in studies using ABI measurement [7], [8], [9], [10] compared to clinical palpation of lower limb pulses [11], [12], [13].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this varied prevalence, screening of PAD among adult diabetic patients in SSA is infrequent [11], [13].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are not supported by the literature [9,10] in which patients suffering from chronic complications of diabetes are usually overweigh subjects with advancing age. Regarding the relationship between types of DM and incidence and severity of microvascular complications, severe complications were frequently reported in patients with Type 1 DM [11][12][13]. Literature evidence also shows positive association between BMI and the development of microvascular complications [50,[55][56][57].…”
Section: Major Microvascular Complications and Associated Factorsmentioning
confidence: 99%
“…Such complications include diabetic foot, renal disease, eye problem, cardiovascular disease, neuropathy, and skin and/or subcutaneous infections [6][7][8][9][10]. In the western world, DM is the leading cause of blindness, non-traumatic lower limb amputation and chronic renal failure, which are on very much increase [11][12][13]. The situation in developing world, particularly in Africa, is even worse due to late diagnosis and poor access to diabetic care [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%